Testicular ischemia in deficiency of adenosine deaminase 2 (DADA2) - Katherine Clarke; Cathy Campbell; Ebun Omoyinmi; Ying Hong; Muthana Al Obaidi; Neil Sebire; Paul A. Brogan (Pediatric Rheumatology Online Journal, 2019)
Abstract Background Deficiency of adenosine deaminase 2 (DADA2) is a rare autosomal recessive autoinflammatory condition. Recognised features include vasculitis predominantly affecting medium sized vessels, livedoid skin rash, central and peripheral nervous system involvement, variable degrees of immunodeficiency, and marrow failure, amongst other clinical presentations. We present the case of a six year old male with DADA2 who presented with acute testicular ischaemia secondary to vasculitis, the first such description in DADA2. Case presentation A six year old male presented acute right-sided testicular pain. His history included transient infantile neutropenia, resolved hepatosplenomegaly, and longstanding livedo racemosa, leading to screening and confirmation of DADA2 caused by homozygous c.139G > C (p.G47R) mutation of ADA2. As his only clinical feature was that of mild livedo racemosa with normal laboratory parameters at diagnosis, he was being actively monitored prior to starting any treatment. At a routine clinic follow-up a 24 h history of testicular pain was noted on systems review. He was afebrile, and his only physical signs were that of moderate livedo racemosa, and tenderness of the right testicle. Laboratory parameters revealed C-reactive protein (CRP) 8 mg/L (reference range [RR] < 20 mg/L); erythrocyte sedimentation rate (ESR) 28 mm/hr. (RR < 10); and serum amyloid A (SAA)5 mg/L (RR < 10). Ultrasound-scan of the scrotum revealed significantly reduced perfusion of the right testes, without torsion. Surgical scrotal exploration confirmed testicular ischaemia without torsion. Histology demonstrated ischaemic seminiferous tubules with intervening haemorrhage and acute inflammatory cells, consistent with vasculitis of the testis as the cause. He was treated with high dose intravenous methyl-prednisolone followed by a weaning course of oral prednisolone, and subcutaneous adalimumab (anti-tumour necrosis factor alpha, anti-TNFα). Repeat ultrasound-scan 3 weeks later revealed good testicular perfusion, with a small area of focal infarction. At last follow-up (11 months post-event) he remained asymptomatic, on treatment with adalimumab. Conclusion The phenotype of DADA2 continues to expand, and we add testicular infarction to the features of DADA2. CRP and SAA cannot be relied on as reliable biomarkers to predict tissue ischaemia and hence who to target for anti-TNFα therapy in DADA2, since these remained steadfastly normal before, during, and after testicular infarction in this case.